1986
DOI: 10.1002/tcm.1770060506
|View full text |Cite
|
Sign up to set email alerts
|

Failure of epoxide formation to influence carbamazepine‐induced teratogenesis in a mouse model

Abstract: The teratogenic potential of the anticonvulsant drug carbamazepine was determined following chronic oral administration in two inbred mouse strains (SWR/J and LM/Bc). The drug was administered in the animal's diet in concentrations equivalent to 0, 1,000, 1,500, or 2,000 mg/kg body weight, with treatment starting 2 wks prior to mating and continuing throughout gestation. Fetal examination failed to reveal a significant pattern of malformation in either strain at any treatment level. Levels of plasma carbamazep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Similar findings were found in study after the exposure to higher doses (1.000, 1.500 and 2.000 mg/kg). In those doses no specific pattern of malformation and no correlation between detected anomalies and dose were found (Finnel et al, 1986). The finding was supported also by following studies (Wray et al, 1982;Fritz et al, 1976).…”
Section: Carbamazepine (Cbz)supporting
confidence: 78%
“…Similar findings were found in study after the exposure to higher doses (1.000, 1.500 and 2.000 mg/kg). In those doses no specific pattern of malformation and no correlation between detected anomalies and dose were found (Finnel et al, 1986). The finding was supported also by following studies (Wray et al, 1982;Fritz et al, 1976).…”
Section: Carbamazepine (Cbz)supporting
confidence: 78%
“…Further studies showed small increases in the rate of cleft palate, dilated cerebral ventricles and growth retardation in mouse foetuses that were similarly treated during the period of organogenesis [Eluma et al, 1981; Eluma, 1984; Paulson et al, 1979; Sullivan et al, 1977]. When mice were chronically exposed to CBZ in their diet prior to and throughout gestation, a significant number of fetuses with congenital defects of the central nervous system or urogenital system were observed [Finnell et al, 1986a]. In experiments comparing teratogenicity of CBZ with other anticonvulsant drugs, it was consistently less teratogenic than phenytoin or primidone [El-Sayed et al 1983; Eluma et al, 1984; Sullivan et al, 1977].…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Small increases in the rate of cleft palate, dilated cerebral ventricles and growth retardation were observed in mouse fetuses that were similarly treated during the period of organogenesis [72–75]. In mice chronically exposed to CBZ in their diet prior to and throughout gestation, a significant number of fetuses were observed with congenital defects of the CNS or urogenital system [76]. In experiments comparing teratogenicity of CBZ with other anticonvulsant drugs, it was consistently less teratogenic than PHT or primidone [72,74,77].…”
Section: Mechanisms Of Aed Teratogenicitymentioning
confidence: 99%